Validation, Reliability, and Usefulness of the Functional Agility Square Test [FAST] - Romina Müller; Daniel Büchel; Jochen Baumeister (Journal of Functional Morphology and Kinesiology)
Background: Agility is crucial in game sports, requiring both motor and cognitive skills. Athletes must perceive and process information to adapt movements, yet traditional agility tests often lack cognitive and multidirectional demands. Additionally, modern test systems are mostly stationary. This study evaluated the novel and portable “Functional Agility Square Test” (FAST) for validity, reliability, and usefulness. Methods: To assess discriminant validity, 22 game sports (GS) and 22 non-game sports (NGS) athletes participated in one session. Test–retest reliability was examined with 36 GS athletes (20 female) across three sessions. Participants performed cognitive (FAST_COG), preplanned (FAST_MOT), and randomized (FAST_SAT) reactive change-of-direction tasks, each repeated three times per session. Results: Results showed significantly lower response times (RTs) in GS compared to NGS (p < 0.05). Mean RTs indicated moderate relative reliability (ICC 0.50–0.74), while medians showed moderate to good reliability (ICC 0.59–0.83). Usefulness was evident from the first session (FAST_MOT) or from the third session (FAST_SAT) based on median RTs. Conclusions: Thus, the FAST seems to be valid, reliable, and sensitive for GS-based agility assessment. Its portable setup enables ecologically valid field testing. Future research should further increase task complexity to better simulate game conditions.